1999
DOI: 10.1523/jneurosci.19-21-09192.1999
|View full text |Cite
|
Sign up to set email alerts
|

A2AAdenosine Receptor Deficiency Attenuates Brain Injury Induced by Transient Focal Ischemia in Mice

Abstract: Extracellular adenosine critically modulates ischemic brain injury, at least in part through activation of the A(1) adenosine receptor. However, the role played by the A(2A) receptor has been obscured by intrinsic limitations of A(2A) adenosinergic agents. To overcome these pharmacological limitations, we explored the consequences of deleting the A(2A) adenosine receptor on brain damage after transient focal ischemia. Cerebral morphology, as well as vascular and physiological measures (before, during, and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
419
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 496 publications
(442 citation statements)
references
References 47 publications
23
419
0
Order By: Relevance
“…Similar observations were made by von Lubitz in a similar gerbil model of brain ischemia [227]. However, this concept of A 2A R blockade as a neuroprotective strategy was difficult to understand at the time and consequently was not widely accepted until the group of Ongini and the group of Chen demonstrated that both the pharmacological blockade of A 2A Rs with a selective antagonist (SCH 582610) [228] as well as the genetic inactivation of A 2A Rs (using A 2A R knockout mice) [229] conferred a robust neuroprotection in animal models of focal ischemia.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations were made by von Lubitz in a similar gerbil model of brain ischemia [227]. However, this concept of A 2A R blockade as a neuroprotective strategy was difficult to understand at the time and consequently was not widely accepted until the group of Ongini and the group of Chen demonstrated that both the pharmacological blockade of A 2A Rs with a selective antagonist (SCH 582610) [228] as well as the genetic inactivation of A 2A Rs (using A 2A R knockout mice) [229] conferred a robust neuroprotection in animal models of focal ischemia.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
“…Interestingly, this neuroprotection afforded by A 2A R blockade was more robust in cortical regions than in the basal ganglia, where these A 2A Rs are considerably more abundant [228,229,231]. This emphasises again that the Fabnormal_ high density of A 2A Rs in striatal medium spiny neurons of the indirect pathway fulfils a very particular role in the control of striatal circuitry and that our knowledge about striatal A 2A Rs should not be extrapolate to understand the general role of A 2A Rs in the brain.…”
Section: A 2a Receptor Blockade Confers Robust Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, mice lacking A2AR (Chen et al, 1999;Ledent et al, 1997) have been shown to demonstrate reduced sensitivity to the hypnotic effects of alcohol, increased alcohol consumption, and reduced alcohol-withdrawal seizures (El Yacoubi et al, 2001;Naassila et al, 2002). As a result, antagonism of A2AR signaling could be useful in the treatment of alcohol withdrawal symptoms; however, since inhibition of A2AR also results in increased alcohol consumption, the mechanisms through which the A2AR mediates each of these effects should be further delineated to identify a more specific therapeutic approach.…”
Section: Adenosine Receptor Signaling In Ethanol Drinkingmentioning
confidence: 99%
“…The rat was the target animal species, as it was the most suitable to study the behavioral effects of intrastriatal administration of cannabinoid agonists. A 2A receptor KO and CB 1 receptor KO mice were generated as described elsewhere (Ledent et al, 1999;Chen et al, 1999). All animals used in a given experiment originated from the same breeding series, and were matched for age and weight.…”
Section: Immunohistochemistrymentioning
confidence: 99%